2016
DOI: 10.1186/s13054-016-1226-4
|View full text |Cite
|
Sign up to set email alerts
|

Applying the termination of resuscitation rules to out-of-hospital cardiac arrests of both cardiac and non-cardiac etiologies: a prospective cohort study

Abstract: BackgroundThe 2015 American Heart Association Guidelines for Cardiopulmonary Resuscitation recommend Basic Life Support (BLS) and Advanced Life Support (ALS) rules for termination of resuscitation (TOR). However, it is unclear whether the TOR rules are valid for out-of-hospital cardiac arrests (OHCAs) of both cardiac and non-cardiac etiologies. In this study, we validated the TOR rules for OHCA resulting from both etiologies.MethodsThis was a prospective multicenter observational study of OHCA patients transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
3
32
1
Order By: Relevance
“…This may be particularly important for patients transported to a hospital with prolonged and ongoing CPR during transport (17). No such data are reported in the study by Kashiura et al (13).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…This may be particularly important for patients transported to a hospital with prolonged and ongoing CPR during transport (17). No such data are reported in the study by Kashiura et al (13).…”
mentioning
confidence: 97%
“…In a prospective multi-center observational study (SOS Kanto 2012) of OHCA patients transported to 67 emergency hospitals between January 2012 and March 2013 in the Kanto region of Japan, the BLS and ALS TOR rules for OHCA resulting from both cardiac and non-cardiac etiologies were again validated (13). Ambulance crews included three EMS providers, with at least one emergency lifesaving technician (ELST) as the highest qualification capable of performing standard ALS interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 452 patients with OHCA who were transported to 67 emergency hospitals by EMS personnel were included in this prospective, multicenter, observational study 11, 12, 13, 14, 15, 16. In this study, patients treated with mCPR devices during advanced cardiovascular life support in the ED were compared with patients who received manual CPR alone.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection of this study has been reported previously 11, 12, 13, 14, 15, 16. The prehospital information was collected by EMS providers.…”
Section: Methodsmentioning
confidence: 99%